Native T1 and T2 provide distinctive signatures in hypertrophic cardiac conditions – Comparison of uremic, hypertensive and hypertrophic cardiomyopathy. (1st May 2020) - Arcari, Luca; Hinojar, Rocio; Engel, Juergen; Freiwald, Tilo; Platschek, Steffen; Zainal, Hafisyatul; Zhou, Hui; Vasquez, Moises; Keller, Till; Rolf, Andreas; Geiger, Helmut; Hauser, Ingeborg; et al.
Abstract: Aims: Profound left ventricular (LV) hypertrophy with diastolic dysfunction and heart failure is the cardinal manifestation of heart remodelling in chronic kidney disease (CKD). Previous studies related increased T1 mapping values in CKD with diffuse fibrosis. Native T1 is a non-specific readout that may also relate to increased intramyocardial fluid. We examined concomitant T1 and T2 mapping signatures and undertook comparisons with other hypertrophic conditions. Methods: In this prospective multicentre study, consecutive CKD patients (n = 154) undergoing routine clinical cardiac magnetic resonance (CMR) imaging were compared with patients with hypertensive (HTN, n = 163) and hypertrophic cardiomyopathy (HCM, n = 158), and normotensive controls (n = 133). Results: Native T1 was significantly higher in all patient groups, whereas native T2 in CKD only (p < 0.001 vs. all groups). Native T1 and T2 were interrelated in patient groups and the strength of association was condition-specific (CKD r = 0.558, HTN r = 0.324, both p < 0.001; HCM r = 0.157, p = 0.05). Native T1 and T2 were similarly correlated in all CKD stages (S3 r = 0.501, S4 0.586, S5 r = 0.424, p < 0.001 for all). Native T1 was the strongest myocardial discriminator between patients and controls (area under the curve, AUC HCM: 0.97; CKD: 0.97, HTN 0.98), native T2 between CKD vs HCM (AUC 0.90) and native T1 and T2 between CKD vs HTN (AUC: 0.83 and 0.80 respectively), p < 0.001 for all. Conclusions: Our findings reveal different CMR signatures of common hypertrophic cardiac phenotypes. Native T1 was raised in all conditions, indicating the presence of pathologic hypertrophic remodelling. Markedly raised native T2 was CKD-specific, suggesting a prominent role of intramyocardial fluid. Highlights: We provide novel insight into the pathologic remodelling secondary to chronic kidney disease (CKD) By CMR T1 and T2 mapping we reveal distinct biosignatures of CKD as compared to healthy controls and hypertrophic phenotypes Diffuse fibrosis is signified by raised native T1 Prominent role of intramyocardial fluid is suggested by raised native T2